Wound infection monitoring and repairing gel dressing containing microspheres
By introducing sodium sodium alginate hydrogel and polyacrylamide-alginate dual-network gels in wound monitoring and repair gel dressing, combined with acid-base indicator and near-infrared light irradiation technology, it solved The existing technologies have insufficient wound infection monitoring and drug control, which realize real -time infection monitoring and precise treatment of wounds, which significantly improves the healing speed and antibacterial effect.
Patent Information
- Application Number
- CN202411339497.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-18
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-25
AI Technical Summary
Existing hydrogel dressings are difficult to achieve accurate monitoring of infection and precisely controlled release of drugs in the prevention and treatment of wound infection, resulting in poor treatment results.
Use microspheres containing wound infection monitoring and repairing gel dressing. This gel dressing consists of sodium sulfide alginate hydrogel and polyacrylamide-alginate dual-network gel. The pH value of the wound surface changes, and under the near -infrared light, the microscopic gel microfotalized hydrogen peroxide is decomposed to produce the activity of liberal radicals to kill the pathogenic microorganism.
Real -time monitoring and precise treatment of facial infections are achieved, which significantly improves the antibacterial ability, promotes the rapid healing of the wound, and reduces the occurrence of pus.
Smart Images

Figure HDA0005059284520000011 
Figure HDA0005059284520000012 
Figure HDA0005059284520000021
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedicine, and more specifically, to a microsphere-containing wound infection monitoring and repairing gel dressing. Background Art
[0002] Severe wound injuries, such as acute wounds such as trauma and burns, or chronic wounds such as diabetes and pressure sores, are often accompanied by complications such as bacterial infection, which seriously hinders the effective healing of wounds and even causes severe sepsis and death. At present, the use of antibacterial drugs is still a common choice for local disinfection of wounds. In clinical treatment, various antibacterial preparations, including antibiotics (such as tetracyclines, penicillins and streptomycin), metal compounds (such as silver nitrate, bismuth thiolate and copper nicotinate), quaternary ammonium salts, peptides, etc., have been widely used to combat bacterial infections. However, the antibacterial process of these antibacterial preparations is usually difficult to control accurately. In order to quickly suppress infection, overdose of antibacterial agents often occurs in actual treatment. In most cases, the abuse or overuse of antibacterial drugs has been generally considered to have an important relationship with bacterial resistant infections and adverse reactions caused by treatment. In view of the above problems, new strategies for wound infection prevention and treatment are constantly being explored. Among them, researchers have found that combining existing antibacterial preparations with hydrogel wound dressings is expected to improve the therapeutic effect of wound infection prevention and treatment. Because hydrogel dressings can not only provide a temporary hydrophilic physical barrier to resist external bacterial infection, but also maintain a moist healing environment to promote rapid wound healing. Some hydrogel dressings even have a loose porous structure that can effectively absorb tissue exudate from the wound, improve the oxygen exchange capacity of the wound, and guide the rapid reconstruction of wound tissue.
[0003] In terms of literature reports, in 2021, Professor Wu Xiaoyang from the University of Chicago and Professor Zhu Linyong's team from East my country University of Science and Technology invented a light-induced imine cross-linked hydrogel wound dressing that can release transforming growth factor-β (TGF-β) inhibitors within a specific time after the wound appears, and successfully achieved scarless wound healing in mouse and large animal preclinical models. In 2022, Professor Guo Baolin of Xi'an Jiaotong University successfully developed a self-healing hydrogel with good conductivity and antioxidant activity based on quaternized chitosan, oxidized dextran, tobramycin and polydopamine-coated polypyrrole nanowires. In 2023, Du Yongzhong's team from Zhejiang University collaborated to develop a new type of extracellular matrix hydrogel. By incorporating exosomes derived from adipose-derived mesenchymal stem cells into the extracellular matrix hydrogel, the exosomes can be continuously released from the hydrogel, significantly increasing the concentration of exosomes at the wound and promoting rapid recovery of the wound surface. Related research results show that the hydrogel can effectively reduce inflammatory response, accelerate the proliferation and migration of wound cells, promote the formation of new blood vessels, improve collagen deposition in the wound area, and accelerate wound repair. Although there have been significant breakthroughs in the use of hydrogel dressings to treat wound infections, existing research technologies still make it difficult to achieve the real-time monitoring and precise on-demand treatment technology strategy proposed in this patent.
[0004] In the existing patent (a skin injury repair hydrogel dressing and its preparation method, CN117357693B), the inventors used polypeptides, cordycepin and oxidized hyaluronic acid to synthesize a skin injury repair hydrogel, which can remove reactive oxygen in damaged tissues and produce nitric oxide, promote the migration function of vascular endothelial cells after radiation damage, significantly reduce cell DNA damage, enhance the stability of cordycepin in tissues, reduce vascular endothelial cell aging, and promote skin injury repair. The invention patent (an antibacterial hydrogel material and its preparation method, CN117582537A) prepared a hydrogel with high-efficiency antibacterial function, which can effectively maintain a microenvironment suitable for wound healing, promote the proliferation and differentiation of fibroblasts, accelerate the generation of new blood vessels and the reconstruction process of wound granulation tissue, and promote the healing process of the wound. The invention patent (protein hybrid gel dressing of composite drug-loaded fiber and its preparation method and application, CN116942891A) discloses a protein hybrid gel dressing of composite drug-loaded fiber, which is mainly composed of a hybrid hydrogel and a loaded hydrophobic antibiotic uniformly dispersed in the gel, wherein the hydrophobic antibiotic can be sustained-released from the gel dressing to achieve long-term antibacterial effect.
[0005] However, most of the hydrogel dressings currently used for wound infection prevention and treatment use a concentration-dependent drug diffusion release mechanism to release the loaded antibacterial drugs to the wound site for antibacterial purposes. The release process is usually difficult to accurately control, resulting in poor treatment effects. The main technical disadvantages include the following two aspects: 1) The infection of the wound cannot be accurately monitored. Most hydrogel dressings lack the ability to provide feedback on the infection of the wound. It is impossible to indicate whether the wound is infected, or it is impossible to monitor the changes in the process from non-infection to infection in real time, resulting in the inability to detect and treat the infection in the early stages of the wound infection, thus missing the best treatment period. 2) Although the current conventional hydrogel wound infection treatment dressings have the ability to control drug release, they cannot achieve accurate controlled release of drugs, resulting in a mismatch between drug release and the antibacterial treatment needs of the wound. There are problems such as drug release that is too fast or too slow, or excessive drug release, and it is impossible to achieve accurate on-demand treatment of wound infection. Summary of the invention
[0006] In order to overcome the defects of the above-mentioned prior art that the infection of the wound surface cannot be accurately monitored and the precise controlled release of the drug cannot be achieved, the present invention provides a wound infection monitoring and repair gel dressing containing microspheres;
[0007] Another object of the present invention is to provide a method for preparing a wound infection monitoring and repair gel dressing containing microspheres;
[0008] Another object of the present invention is to provide an application of a wound infection monitoring and repair gel dressing containing microspheres.
[0009] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0010] A method for preparing a microsphere-containing wound infection monitoring and repair gel dressing comprises the following steps:
[0011] S1, adding molybdenum disulfide solution to sodium alginate solution, stirring fully, to obtain molybdenum disulfide sodium alginate solution;
[0012] S2, injecting the molybdenum disulfide sodium alginate solution into the calcium chloride solution, standing and cross-linking, to obtain molybdenum disulfide gel microspheres;
[0013] S3, sodium alginate and acrylamide are dissolved in water by stirring, methylene bisacrylamide, polyacrylamide, acid-base indicator and ammonium persulfate are added, and the mixture is fully mixed and dissolved to obtain a mixed solution;
[0014] S4, adding molybdenum disulfide gel microspheres to the mixed solution, and adding tetramethylethylenediamine and calcium sulfate dihydrate in sequence under continuous stirring, and stirring evenly;
[0015] S5. After standing to solidify and removing impurities, a wound infection monitoring and repair gel dressing containing microspheres is obtained.
[0016] Preferably, molybdenum disulfide nanoparticles and sodium alginate are dispersed in deionized water to obtain a molybdenum disulfide solution and a sodium alginate solution respectively;
[0017] Preferably, when dispersing molybdenum disulfide nanoparticles in deionized water, the stirring speed is 100-1000 r / min, and the stirring time is 5-20 min; when dispersing sodium alginate in deionized water, the stirring speed is 50-200 r / min, and the stirring time is 1-3 h.
[0018] Preferably, when the molybdenum disulfide nanoparticles are dispersed in water, the stirring speed is 800 r / min and the stirring time is 10 min; when the sodium alginate is dispersed in water, the stirring speed is 100 r / min and the stirring time is 2 h.
[0019] Furthermore, the concentration of the molybdenum disulfide solution in S1 is 0.01-1 g / mL, and the concentration of the obtained sodium alginate solution is 0.025-0.6 g / mL.
[0020] Preferably, the concentration of the molybdenum disulfide solution obtained in S1 is 0.1 g / mL, and the concentration of the sodium alginate solution obtained is 0.15 g / mL.
[0021] Preferably, in S1, the molybdenum disulfide solution is added to the sodium alginate solution.
[0022] Furthermore, the volume ratio of the molybdenum disulfide solution to the sodium alginate solution added to S1 is 0.1:5-20.
[0023] Preferably, the stirring speed in S1 is 200 to 1000 r / min and the time is 5 to 20 min.
[0024] Preferably, the stirring speed in S1 is 800 r / min and the time is 10 min.
[0025] Furthermore, in S2, the molybdenum disulfide sodium alginate solution is injected into the calcium chloride solution at a flow rate of 0.02 to 1.0 mL / min by external force; the speed generated by the external force is 10.5 to 15.5 m / s.
[0026] Preferably, in S2, the molybdenum disulfide sodium alginate solution is extruded at a flow rate of 0.02 to 1.0 mL / min and blown into the calcium chloride solution by wind force; the wind speed is 10.5 to 15.5 m / s.
[0027] Preferably, the flow rate is 0.1 mL / min and the wind speed is 12.5 m / s.
[0028] Preferably, blowing is performed using a microsyringe pump.
[0029] Furthermore, the mass percentage of the calcium chloride solution in S2 is 0.5% to 2%.
[0030] Preferably, the mass percentage of the calcium chloride solution in S2 is 1.5%.
[0031] Preferably, the standing time in S2 is 10 to 50 minutes.
[0032] Preferably, the standing time in S2 is 30 min.
[0033] Preferably, after standing, the molybdenum disulfide gel microspheres are rinsed to be redispersed in deionized water.
[0034] Furthermore, in the mixed solution of S3, the concentration of sodium alginate is 0.01-0.04 g / mL, the concentration of acrylamide is 0.05-0.25 g / mL, the concentration of methylene bisacrylamide is 0.05-0.15 mg / mL, the concentration of polyacrylamide is 0.5-3 mg / mL, the concentration of acid-base indicator is 0.05-0.5 mg / mL, and the concentration of ammonium persulfate is 0.5-3 mg / mL.
[0035] Preferably, in the mixed solution of S3, the concentration of sodium alginate is 0.025 g / mL, the concentration of acrylamide is 0.135 g / mL, the concentration of methylenebisacrylamide is 0.085 mg / mL, the concentration of polyacrylamide is 1 mg / mL, the concentration of the acid-base indicator is 0.2 mg / mL, and the concentration of ammonium persulfate is 1.5 mg / mL.
[0036] Preferably, the acid-base indicator is phenol red.
[0037] Preferably, the stirring time of sodium alginate and acrylamide in S3 is 3 hours.
[0038] Preferably, during the thorough mixing and dissolution in S3, the stirring speed is 200 to 1000 r / min and the stirring time is 5 to 50 min.
[0039] Preferably, during the thorough mixing and dissolution in S3, the stirring speed is 500 r / min and the stirring time is 30 min.
[0040] Furthermore, after S4 is stirred evenly, the concentration of molybdenum disulfide gel microspheres is 0.2-0.8 g / mL, the concentration of tetramethylethylenediamine is 0.3-2 μL / mL, and the concentration of calcium sulfate dihydrate is 0.001-0.01 g / mL.
[0041] Preferably, after S4 is stirred evenly, the concentration of molybdenum disulfide gel microspheres is 0.4 g / mL, the concentration of tetramethylethylenediamine is 1.5 μL / mL, and the concentration of calcium sulfate dihydrate is 0.004 g / mL.
[0042] Preferably, in S4, the mixed solution is first subjected to a defoaming treatment.
[0043] Preferably, tetramethylethylenediamine is added to S4 and stirred for 2 to 10 minutes, and then calcium sulfate dihydrate powder is slowly added through a sieve while stirring.
[0044] Preferably, the screen is 100 mesh.
[0045] Preferably, the standing time in S5 is 1 to 3 days.
[0046] Preferably, it is allowed to stand at 4°C for 2 days.
[0047] A microsphere-containing wound infection monitoring and repairing gel dressing is prepared by the preparation method.
[0048] Furthermore, the microspheres are molybdenum disulfide gel microspheres, and the diameter thereof is 300 to 1000 μm.
[0049] An application of the microsphere-containing wound infection monitoring and repair gel dressing, and the application of the microsphere-containing wound infection monitoring and repair gel dressing in the preparation of wound treatment consumables. Preferably, the near-infrared light wavelength is 800-1650nm, the irradiation time is 5-20min, and the concentration of hydrogen peroxide is 10-100mM.
[0050] Preferably, hydrogen peroxide is dripped onto the wound surface, covered with the wound infection monitoring and repair gel dressing containing microspheres, and then irradiated with near-infrared light.
[0051] Changes in pH are crucial for monitoring the state of the wound, as changes in pH indirectly reflect the infection of the wound and the remodeling process of the wound tissue. Normally, acidic keratin sebum and eccrine sweat gland secretions usually form a slightly acidic stratum corneum on the surface of healthy skin, with a pH value mainly ranging from 4.0 to 6.0. However, in infected wounds, due to the action of microorganisms and the presence of bacterial enzymes, the pH value will gradually tend to alkaline, with values mostly distributed between 7.0-9.0.
[0052] Based on this, the present invention uses polyacrylamide-alginate double network gel as the main component of the dressing. On the one hand, the acid-base indicator is used to observe the change of the pH value of the wound surface to realize real-time infection monitoring of the wound surface; on the other hand, the molybdenum disulfide gel microspheres inside the gel dressing can quickly decompose low-concentration hydrogen peroxide under the irradiation of near-infrared laser, and produce active free radicals to kill pathogenic microorganisms in the wound surface, thereby realizing real-time infection monitoring of the wound surface and accurate on-demand antibacterial treatment. At the same time, when the wound surface is not infected, there will be no excessive release of antibacterial drugs, and accurate on-demand treatment can be performed according to the infection situation of the wound surface.
[0053] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0054] 1. Real-time monitoring capability of wound infection: The color change of gel dressing under different pH environments can sensitively reflect the changes in the pH value of the wound, which can help quickly determine whether the wound is infected. When the wound is infected with bacteria, the pH value rises and the color of the gel changes from yellow to red.
[0055] 2. Precise control of on-demand antibacterial treatment: Sodium alginate hydrogel microspheres containing molybdenum disulfide nanomaterials can decompose hydrogen peroxide to produce reactive oxygen (·OH) under near-infrared light irradiation, thereby killing pathogenic microorganisms. The results of antibacterial experiments show that the antibacterial ability can only be significantly improved when low-concentration hydrogen peroxide is used in combination with gel dressings and irradiated with near-infrared lasers. For example, the inhibition rate against Escherichia coli reached 94.44%, against Staphylococcus aureus was 97.80%, against Pseudomonas aeruginosa was 92.68%, and against Acinetobacter baumannii was 85.68%.
[0056] 3. Excellent mechanical properties and adaptability: The gel dressing exhibits good tensile deformation ability and can be stretched to more than 3 times its original length without breaking or releasing the encapsulated microspheres. This property makes it particularly suitable for body parts that require frequent movement or deformation (such as elbows, knees, etc.). The internal structure of the gel dressing of the present invention is loose and porous, which helps to improve the air permeability of the gel and its ability to absorb wound exudate, thereby providing a better environment for wound healing.
[0057] 4. Promote wound healing: After using the gel dressing of the present invention in combination with near-infrared laser irradiation, the wound healing speed is significantly accelerated, the infection is effectively controlled, the production of pus is reduced, and the rapid regeneration of wound tissue is promoted. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 Taking photos for stereo microscope to observe the difference in particle size of MoS2 gel microspheres prepared with different wind speeds;
[0059] Figure 2To observe the tensile deformation performance of gel dressing;
[0060] Figure 3 The scanning electron microscope pictures of the surface and fracture surface of the polyacrylamide-alginate double network gel prepared by the present invention are compared with the polyacrylamide gel;
[0061] Figure 4 Observation of the color change of the gel dressing after being placed in saline with different pH values for 10 minutes;
[0062] Figure 5 The absorbance value of methylene blue was detected by hydrogen peroxide oxidation to promote the decomposition of gel dressing by near infrared laser;
[0063] Figure 6 The plate colony counting method was used to test the efficacy of near-infrared laser-promoted gel dressing decomposition of hydrogen peroxide in inhibiting bacterial growth;
[0064] Figure 7 Observation of bacterial live and dead fluorescence labeling: observation of bacterial live (green fluorescence) and dead (red fluorescence) in gel dressings prepared under low concentration hydrogen peroxide solution without near-infrared laser irradiation and with near-infrared laser irradiation;
[0065] Figure 8 To observe the effect of gel dressing on wound infection in mice at different time periods under different treatment schemes;
[0066] Fig. 9 To take photos of mouse wounds at different time periods and observe how near-infrared laser promotes the gel dressing to decompose hydrogen peroxide, inhibit wound infection and promote wound healing. DETAILED DESCRIPTION
[0067] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0068] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0069] Example 1
[0070] Preparation of microsphere-containing gel dressing for wound infection monitoring and repair
[0071] Step 1: At room temperature, 0.4 g of molybdenum disulfide nanoparticles were added to 4 mL of deionized water, and stirred at a stirring rate of 800 rpm for 10 minutes using a magnetic stirrer to fully disperse the molybdenum disulfide nanoparticles in the aqueous solution.
[0072] Step 2: 1.5 g of sodium alginate powder was sieved and added to 10 mL of deionized water, and stirred at a stirring rate of 100 rpm for 2 hours. After the sodium alginate was fully dissolved, 100 μL of the molybdenum disulfide solution obtained in the first step was taken and added dropwise to the sodium alginate solution, and then stirred at a stirring rate of 800 rpm for 10 minutes to fully mix the molybdenum disulfide solution and the sodium alginate solution.
[0073] Step 3: The molybdenum disulfide sodium alginate solution obtained in the second step is sucked into a syringe, extruded at a flow rate of 0.1 mL / min by a microinjection pump, and blown into a 1.5% (mass percentage) calcium chloride solution by a wind force of 12.5 m / s, and allowed to stand in the solution for 30 minutes. Sodium alginate hydrogel microspheres doped with molybdenum disulfide nanomaterials are obtained in the calcium chloride solution through the cross-linking effect of calcium ions, and then the gel spheres are rinsed three times with deionized water and redispersed in deionized water for standby use.
[0074] Step 4: 2.5 g of sodium alginate powder and 13.5 g of acrylamide were dissolved in 100 mL of deionized water under magnetic stirring for 3 hours, followed by adding 8.5 mg of methylene bisacrylamide, 0.1 g of polyacrylamide, 0.002 g of phenol red powder, and 0.15 g of ammonium persulfate powder, and stirring at a stirring rate of 500 rpm for 30 minutes using a magnetic stirrer to fully mix and dissolve the sample.
[0075] Step 5: After defoaming the mixed solution obtained in the fourth step using an ultrasonic defoamer, 4 g of sodium alginate hydrogel microspheres doped with molybdenum disulfide nanomaterials prepared in the third step are added to each 10 mL of the mixed solution. After adding 15 μL of tetramethylethylenediamine under magnetic stirring and stirring for 5 minutes, 0.04 g of calcium sulfate dihydrate powder is added while stirring through a 100-mesh sieve. After stirring evenly, the mixed solution is poured into a glass mold with a length of 100 mm, a width of 83 mm, and a height of 1.5 mm and placed in a 4-degree Celsius refrigerator for 2 days until the mixed solution is fully cross-linked and polymerized to solidify into a gel. The gel is then removed from the glass mold, soaked in deionized water, and shaken and cleaned in a horizontal dehydration shaker 3 times (10 minutes each time) to remove residual monomers that have not been cross-linked. After cleaning is completed, a wound infection monitoring and treatment gel dressing containing microspheres is finally obtained.
[0076] Performance testing.
[0077] Example 2
[0078] Preparation of microsphere-containing gel dressing for wound infection monitoring and repair
[0079] Step 1: At room temperature, add 0.1 g of molybdenum disulfide nanoparticles into 10 mL of deionized water, and stir the solution at a stirring rate of 100 rpm for 5 minutes using a magnetic stirrer to fully disperse the molybdenum disulfide nanoparticles in the aqueous solution.
[0080] Step 2: Sieve 0.5 g of sodium alginate powder and add it to 20 mL of deionized water, stirring at a stirring rate of 50 rpm for 1 hour. After the sodium alginate is fully dissolved, take 100 μL of the molybdenum disulfide solution obtained in the first step and add it dropwise to the sodium alginate solution, then stir at a stirring rate of 200 rpm for 5 minutes to fully mix the molybdenum disulfide solution and the sodium alginate solution.
[0081] Step 3: The molybdenum disulfide sodium alginate solution obtained in the second step is sucked into a syringe, extruded at a flow rate of 0.02 mL / min by a microinjection pump, and blown into a 0.5% (mass percentage) calcium chloride solution by a wind force of 15.5 m / s, and allowed to stand in the solution for 50 minutes. Sodium alginate hydrogel microspheres doped with molybdenum disulfide nanomaterials are obtained in the calcium chloride solution through the cross-linking effect of calcium ions, and then the gel spheres are rinsed three times with deionized water and redispersed in deionized water for standby use.
[0082] Step 4: 1 g of sodium alginate powder and 25 g of acrylamide were dissolved in 100 mL of deionized water under magnetic stirring for 3 hours, followed by adding 15 mg of methylene bisacrylamide, 0.05 g of polyacrylamide, 0.05 g of phenol red powder, and 0.3 g of ammonium persulfate powder, and stirring at a stirring rate of 200 rpm for 5 minutes using a magnetic stirrer to fully mix and dissolve the sample.
[0083] Step 5: After defoaming the mixed solution obtained in the fourth step using an ultrasonic defoamer, 8g of sodium alginate hydrogel microspheres doped with molybdenum disulfide nanomaterials prepared in the third step are added to each 10mL of the mixed solution. After adding 3μL of tetramethylethylenediamine under magnetic stirring and stirring for 2 minutes, 0.1g of calcium sulfate dihydrate powder is added while stirring through a 100-mesh sieve. After stirring evenly, the mixed solution is poured into a glass mold with a length of 100mm, a width of 83mm, and a height of 1.5mm and placed in a 4-degree Celsius refrigerator for 3 days until the mixed solution is fully cross-linked and polymerized to solidify into a gel. The gel is then removed from the glass mold, soaked in deionized water, and shaken and cleaned in a horizontal dehydration shaker 3 times (10 minutes each time) to remove residual monomers that have not been cross-linked. After cleaning is completed, a wound infection monitoring and treatment gel dressing containing microspheres is finally obtained.
[0084] Performance testing.
[0085] Example 3
[0086] Preparation of microsphere-containing gel dressing for wound infection monitoring and repair
[0087] Step 1: At room temperature, add 10 g of molybdenum disulfide nanoparticles into 10 mL of deionized water, and stir the solution at a stirring rate of 1000 rpm using a magnetic stirrer for 20 minutes to fully disperse the molybdenum disulfide nanoparticles in the aqueous solution.
[0088] Step 2: 12 g of sodium alginate powder was sieved and added to 20 mL of deionized water, and stirred at a stirring rate of 200 rpm for 3 hours. After the sodium alginate was fully dissolved, 100 μL of the molybdenum disulfide solution obtained in the first step was taken and added dropwise to the sodium alginate solution, and then stirred at a stirring rate of 1000 rpm for 20 minutes to fully mix the molybdenum disulfide solution and the sodium alginate solution.
[0089] Step 3: The molybdenum disulfide sodium alginate solution obtained in the second step is sucked into a syringe, extruded at a flow rate of 1 mL / min by a microinjection pump, and blown into a 2% (mass percentage) calcium chloride solution by a wind force of 12.5 m / s, and allowed to stand in the solution for 10 minutes. Sodium alginate hydrogel microspheres doped with molybdenum disulfide nanomaterials are obtained in the calcium chloride solution through the cross-linking effect of calcium ions, and then the gel spheres are rinsed three times with deionized water and redispersed in deionized water for standby use.
[0090] Step 4: 4 g of sodium alginate powder and 5 g of acrylamide were dissolved in 100 mL of deionized water under magnetic stirring for 3 hours, followed by adding 5 mg of methylene bisacrylamide, 0.3 g of polyacrylamide, 0.005 g of phenol red powder, and 0.05 g of ammonium persulfate powder, and stirring at a stirring rate of 1000 rpm for 50 minutes using a magnetic stirrer to fully mix and dissolve the sample.
[0091] Step 5: After defoaming the mixed solution obtained in the fourth step using an ultrasonic defoamer, 2g of sodium alginate hydrogel microspheres doped with molybdenum disulfide nanomaterials prepared in the third step are added to each 10mL of the mixed solution. After adding 20μL of tetramethylethylenediamine under magnetic stirring and stirring for 2 minutes, 0.01g of calcium sulfate dihydrate powder is slowly added while stirring through a 100-mesh sieve. After stirring evenly, the mixed solution is poured into a glass mold with a length of 100mm, a width of 83mm, and a height of 1.5mm and placed in a 4-degree Celsius refrigerator for 1 day until the mixed solution is fully cross-linked and polymerized to solidify into a gel. The gel is then removed from the glass mold, soaked in deionized water, and shaken and cleaned in a horizontal shaker 3 times (10 minutes each time) to remove residual monomers that have not been cross-linked. After cleaning is completed, a wound infection monitoring and treatment gel dressing containing microspheres is finally obtained.
[0092] Performance testing.
[0093] Example 4
[0094] Preparation of MoS2 Gel Microspheres
[0095] 0.5g of molybdenum disulfide was dispersed in 4mL of deionized water and stirred continuously for 10 minutes at 1000 rpm using a magnetic stirrer. Afterwards, 100 μL of the molybdenum disulfide solution obtained was added dropwise to 5mL of 1.5% (mass volume ratio) of sodium alginate solution under a stirring condition of 800 rpm, and continued to stir for 10 minutes to obtain a uniform solution. Subsequently, the mixture was sprayed into 3 liters of 1.5% (mass volume ratio) of calcium chloride solution by a microinjection pump extrusion device at an extrusion flow rate of 0.1mL / min under a wind force of 13.5m / s to obtain gel microspheres containing molybdenum disulfide nanomaterials of different particle sizes.
[0096] Embodiments 5 to 8
[0097] The technical solutions of Examples 5 to 8 are similar to that of Example 4, except that the wind forces of Examples 5 to 6 are 14.5 m / s, 15.5 m / L, 10.5 m / s and 11.5 m / L, respectively.
[0098] Comparative Example 1
[0099] Conventional polyacrylamide gel, the specific preparation method is as follows: add 4.1mL of deionized water into a 30mL beaker, then add 30% Acr-Bis (29:1) 3.3mL, lower gel buffer (4×) 2.5mL, 10% gel polymerization catalyst 0.1mL purchased from Biyuntian Biotechnology Co., Ltd. in the polyacrylamide gel preparation kit, stir evenly, quickly pour into the 1.5mm thick electrophoresis gel preparation glass plate interlayer, carefully remove bubbles, and inject deionized water until the top of the interlayer glass plate. After standing for 1h, a 10% concentration SDS-PAGE gel is obtained.
[0100] Detection Methods
[0101] 1. Particle size observation
[0102] Stereo microscope photography was used to observe the particle size of molybdenum disulfide gel microspheres prepared using different wind speeds.
[0103] 2. Testing of tensile deformation properties of gel dressings
[0104] The gel dressing prepared in Example 1 was cut into strips with a length of 130 mm, a width of 23 mm, and a thickness of 1.5 mm, and stretched by holding the two ends of the gel.
[0105] 3. Observation of microstructure of gel dressing
[0106] The surface and fracture surface of the gels of Example 2 and Comparative Example 1 were observed by scanning electron microscopy.
[0107] 4. Observation of the performance of gel dressing in indicating pH changes
[0108] The gel dressing prepared in Example 3 was placed in phosphate buffer solutions of different pH values for 10 minutes and then taken out. The gel showed obvious color changes.
[0109] 5. Detection of active free radicals
[0110] Methylene blue reagent was used to detect the generation of active free radical ·OH in the solution, and near-infrared laser was used to promote the decomposition of the gel dressing and the absorbance value of hydrogen peroxide oxidized methylene blue was detected.
[0111] 6. Antibacterial efficacy test
[0112] The antibacterial properties of the prepared gel dressings were tested using Escherichia coli (E. coli, Gram-negative bacteria), Pseudomonas aeruginosa (P. aeruginosa, Gram-negative bacteria), Acinetobacter baumannii (A. baumannii, Gram-negative bacteria) and Staphylococcus aureus (S. aureas, Gram-positive bacteria), which are common in wounds, as representative model bacteria. First, the single colonies of the above four model bacteria were incubated in 5 mL of sterile bacterial broth medium (purchased from Aladdin Company), and the shaking speed of the bacterial culture shaker was 250 rpm, and the shaking was maintained at 37°C overnight to obtain a bacterial suspension in the logarithmic phase. Subsequently, the bacterial suspensions were transferred to new test tubes and diluted step by step to a bacterial concentration of 1×10 using sterile bacterial broth medium at a dilution multiple of 10. 6 After that, the four bacterial suspensions were divided into centrifuge tubes, centrifuged at 4000 rpm for 5 minutes, the bacterial culture medium was removed, and the bacteria were resuspended in sterile phosphate buffer to a bacterial concentration of 1×10 6CFU / mL. Subsequently, 1 mL of the bacterial suspension was added to the culture wells of a 24-well cell culture plate and further divided into the following six groups: (I) bacteria alone group, (II) bacteria + H2O2 group (the concentration of H2O2 was 20 mM), (III) bacteria + H2O2 + near-infrared laser irradiation group (the concentration of H2O2 was 20 mM, the 808 nm near-infrared laser irradiation power was 1.5 watts per square centimeter, and the irradiation time was 10 minutes), (IV) bacteria + gel dressing group, (V) bacteria + H2O2 + gel dressing group, and (VI) bacteria + H2O2 + gel dressing + near-infrared laser irradiation group. After incubation for 10 minutes or near-infrared laser irradiation for 10 minutes, the above groups were diluted twice with sterile phosphate buffer at a dilution factor of 10, and 100 μl of the diluted bacterial suspension was spread on the surface of a sterile bacterial agar plate. The plate was cultured in a bacterial incubator at 37°C for 24 hours, and the plate was taken out for photography, followed by colony counting and statistical analysis.
[0113] 7. Fluorescence staining observation
[0114] A commercial bacterial live-dead fluorescent staining kit (purchased from Invitrogen) was used to stain and observe the bacteria after using the gel dressing of Example 1 in a low concentration hydrogen peroxide solution (20 mM) and after using the gel dressing in combination with near-infrared laser irradiation for 10 minutes (1.5 watts per square centimeter).
[0115] 8. Ability to monitor wound infection
[0116] A mouse full-thickness skin defect model and a mouse full-thickness skin defect model infected with Staphylococcus aureus were constructed respectively. C57 male mice (8 weeks) were anesthetized by continuous inhalation of 1.5% isoflurane by an animal anesthesia machine in the form of inhalation anesthesia. Subsequently, the hair on the back of the mouse was removed using a shaving clipper, and then the back was depilated using a purchased commercial depilatory cream (Veet, Reckitt Benckiser). Before the operation, the skin surface was disinfected with iodine solution and 75% alcohol, respectively. Subsequently, a circular full-thickness skin layer with a diameter of 10±2mm was excised on the back of each mouse using a scalpel and surgical scissors, and the wound was rinsed with sterile saline to remove the exuded blood. After that, the mice were divided into groups, among which the mice with sterile phosphate buffer added to the wound site were used as the non-infected group (negative control group), and 20μL of Staphylococcus aureus suspension diluted with sterile phosphate buffer (10 6 The wounds of the two groups of mice were covered with the gel dressings prepared in Example 1, and sealed with 3M polyacrylamide film, and the color changes of the gel dressings were observed after 1 day, 2 days, and 3 days.
[0117] 9. Inhibition of wound infection
[0118] The wound surfaces of mice were photographed at different time periods to observe how near-infrared laser promoted the gel dressing to decompose hydrogen peroxide, inhibiting wound infection and promoting wound healing.
[0119] Test results
[0120] 1. Particle size observation
[0121] The particle size of the molybdenum disulfide gel microspheres in Examples 4 to 8 is as follows: Figure 1 As shown. When the wind speed at the needle tip is 10.5m / s (Example 7), the average particle size of the gel microspheres is 951.4 microns. When the wind speed at the needle tip is 11.5m / s (Example 8), the average particle size of the gel microspheres is reduced to 846.97 microns. Within a certain range, as the wind speed increases, the prepared gel particle size gradually becomes smaller. When the wind speed reaches 13.5m / s (Example 4), the average particle size of the gel microspheres is reduced to 546.30 microns; when the wind speed reaches 14.5m / s (Example 5), the average particle size of the gel microspheres is reduced to 389.25 microns. When the wind speed reaches 15.5m / s (Example 6), the size of the gel ball particle size no longer shows a linear relationship with the increase in wind force. If the particle size is too small, the molybdenum disulfide content in the microspheres is less, which is not conducive to the subsequent rapid decomposition of hydrogen peroxide to kill bacteria under near-infrared light irradiation. If the particle size is too large, it will affect the visual observation of the color change of the gel and affect the cross-linking preparation of the gel. The concentration of alginate, the extrusion rate of the microinjection pump and the wind force of the needle tip of the present invention are matched within a suitable interval range to obtain gel microspheres with smaller particle sizes, which are more conducive to the performance of the gel dressing.
[0122] 2. Testing of tensile deformation properties of gel dressings
[0123] like Figure 2 As shown, the tensile deformation capacity of the gel dressing prepared in Example 1 can reach more than 3 times the original length, and compared with conventional wound gel dressings, it has excellent deformation and stretching capacity. In addition, the black molybdenum disulfide gel microspheres wrapped in the gel also show excellent deformation capacity as the gel is stretched. During the stretching process, the molybdenum disulfide gel microspheres and the gel dressing show good adaptability, and do not separate from the gel due to the significant deformation of the gel dressing. This shows that the prepared gel dressing exhibits excellent tensile deformation capacity, which makes it well suitable for the bending and straightening deformation of the wound, such as the large bending deformation requirements of the elbow and knee joints, so that the gel dressing can adapt well to the deformation displacement of the wound.
[0124] 3. Observation of microstructure of gel dressing
[0125] like Figure 3 As shown, the polyacrylamide-alginate double network hydrogel dressing containing molybdenum disulfide sodium alginate gel balls prepared in Example 2 is significantly different from the conventional polyacrylamide gel of Comparative Example 1. The surface structure of the polyacrylamide gel of Comparative Example 1 is relatively dense, and the pore structure is relatively small. In contrast, the surface of the gel dressing prepared in Example 2 presents a loose gel pore structure, and the number of pores is also significantly improved. When the polyacrylamide gel of Comparative Example 1 and the prepared gel dressing are broken and the fracture section of the gel is observed, it can be found that the internal gel cross-linking of the fracture section of the polyacrylamide gel of Comparative Example 1 is relatively dense, and the number of pores of the gel is small, while the fracture section of the gel dressing of Example 2 is significantly different, and the gel fracture surface presents an obvious honeycomb sponge structure, not only on the surface of the gel, but also in the interior of the gel. It also presents an extremely high porosity. Therefore, with the help of a loose porous structure, the gel dressing prepared by the present invention will have a more excellent deformation and stretching ability, better air permeability and absorption and drainage ability for wound exudate.
[0126] 4. Observation of the performance of gel dressing in indicating pH changes
[0127] like Figure 4 As shown, with the gradual increase of the pH value of the solution from 4.5 to 9.0, the color of the gel prepared in Example 3 gradually changes from the initial yellow to brown. When the solution is alkaline, the gel gradually changes from brown to red and finally reaches dark red. This shows that the gel dressing prepared by the present invention can sensitively respond to changes in pH and reflect the acid-base conditions of the pH environment in which the gel is located through obvious changes in the color of the gel.
[0128] 5. Detection of active free radicals
[0129] Methylene blue is a commonly used hydroxyl radical scavenger. Its working principle is that methylene blue is oxidized by ·OH to generate colorless methylene white, so that the color of the methylene blue solution gradually fades from blue to colorless. Figure 5The ultraviolet absorption curve of the solution sample at 400-800nm shows that no obvious absorption signal can be detected in the 20mM hydrogen peroxide aqueous solution without adding methylene blue. However, the methylene blue solution added with the gel dressing prepared in Example 1 shows the highest absorption value at the same wavelength, indicating that the methylene blue solution does not produce obvious active free radicals ·OH, and the blue methylene blue solution does not fade significantly. When the gel dressing of Example 1 was irradiated with a near-infrared laser of 808nm wavelength at a power of 0.5W / cm2 for 10 minutes, the absorption value of the methylene blue solution decreased, indicating that the generation of active free radicals ·OH in the solution increased, and the methylene blue was oxidized and faded by ·OH. Moreover, under the same conditions, when the power of the irradiation laser was increased from 0.5W / cm2 to 1.0W / cm2, 1.5W / cm2, and 2.0W / cm2, it was found that as the laser irradiation intensity increased, the ability of the prepared gel dressing to decompose hydrogen peroxide to produce ·OH became stronger. It is proved that the use of near-infrared laser irradiation can accurately control and enhance the ability of the gel dressing prepared by the present invention to decompose hydrogen peroxide to produce ·OH.
[0130] 6. Antibacterial efficacy test
[0131] like Figure 6 As shown in the figure, the antibacterial ability of the diluted hydrogen peroxide solution (20mM) is greatly reduced. By counting the bacterial clone colonies in the bacterial culture dish and comparing them with the blank control group, it is found that more than 71.93% of the Escherichia coli, more than 76.80% of the Staphylococcus aureus, more than 85.37% of the Pseudomonas aeruginosa, and more than 78.78% of the Acinetobacter baumannii survive. On this basis, the addition of near-infrared laser irradiation also failed to significantly enhance the antibacterial efficacy of the low-concentration hydrogen peroxide solution. Similarly, when only the gel dressing prepared in Example 1 is used, or the gel dressing is used in combination with low-concentration hydrogen peroxide, no obvious antibacterial effect is observed. Only when the low-concentration hydrogen peroxide is added and the gel dressing is used in combination with 808nm near-infrared laser irradiation, a significant antibacterial effect can be observed. Among them, the inhibition rates of Escherichia coli reached 94.44%, Staphylococcus aureus was 97.80%, Pseudomonas aeruginosa was 92.68%, and Acinetobacter baumannii was 85.68%, showing good antibacterial efficacy, indicating that the use of near-infrared laser irradiation can significantly enhance the antibacterial ability of the gel dressing prepared by the present invention.
[0132] 7. Fluorescence staining observation
[0133] Under a confocal fluorescence microscope, the SYTO-9 green fluorescent nucleic acid dye in the bacterial live-dead fluorescent staining kit can successfully mark the bacteria and show bright green fluorescence. At the same time, there is another red fluorescent nucleic acid dye called propidium iodide (PI) in the kit. Since PI can only penetrate damaged bacterial membranes, and at the same time, the penetration of PI and the insertion staining of bacterial nucleic acids will reduce the green fluorescence signal of the SYTO-9 dye, therefore, according to this principle, bacteria with intact membrane structure and good growth status will show bright green fluorescence under the labeling of the kit, while bacteria with damaged membranes will show red fluorescence. Figure 7 As shown in the figure, under the condition of low concentration hydrogen peroxide solution (20mM), the use of gel dressing alone did not damage the bacteria. Among the four bacteria tested, almost all of them showed bright green fluorescence. On the contrary, after using gel dressing and combining with near-infrared laser irradiation, except for a few green fluorescent spots observed in Acinetobacter baumannii, the other three bacteria all showed obvious red fluorescence, indicating that most of the bacteria were significantly damaged.
[0134] 8. Ability to monitor wound infection
[0135] like Figure 8 As shown in the figure, after the gel dressing was placed on the wound of mice for 1 day, the wound dressing of the non-infected group (normal saline group) without Staphylococcus aureus was yellow-brown, while the wound dressing of the other gel dressing groups with Staphylococcus aureus, H2O2+gel dressing group, and H2O2+gel dressing+near-infrared laser group was pink. By observing the color change of the gel, it was found that the pH value distribution range of the wound of the normal saline group without infection was between 6.0 and 7.0, and the wound of mice infected with Staphylococcus aureus was generally alkaline, with a pH value distribution range of 7.5 to 8.5. This shows that by observing the color change of the wound gel, it is possible to effectively distinguish whether the wound is infected.
[0136] 9. Inhibition of wound infection
[0137] like Fig. 9As shown in the figure, after Staphylococcus aureus infects the wound for 1 day, the dressing changes from the initial bright yellow to rose red, indicating that the wound of the mouse gradually becomes alkaline under the continuous bacterial infection. At the same time, under the same conditions of applying gel, the healing of the wound of the mouse without near-infrared laser irradiation and the wound of the mouse with near-infrared laser irradiation showed obvious differences. The wound of the mouse without near-infrared laser irradiation showed obvious characteristics of wound infection on the third day after Staphylococcus aureus infection, and the wound showed obvious yellow pus, indicating that the wound had been infected and inflamed. In addition, since the infection was not suppressed in time, the inflammation of the wound gradually worsened with the increase of time, which significantly hindered the healing and repair of the wound. In contrast, the inflammation of the wound of the mouse irradiated with near-infrared laser was significantly suppressed on the second day after treatment. Under the same healing time, the healing speed of the wound was significantly better than that of the wound of the mouse without near-infrared laser irradiation, indicating that near-infrared laser can promote the decomposition of hydrogen peroxide by gel dressing to inhibit wound infection and promote wound healing.
[0138] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a microsphere-containing wound infection monitoring and repair gel dressing, characterized in that: The following steps are involved: S1, adding molybdenum disulfide solution to sodium alginate solution, stirring fully, to obtain molybdenum disulfide sodium alginate solution; S2, adding the molybdenum disulfide sodium alginate solution into the calcium chloride solution, standing and cross-linking, to obtain molybdenum disulfide gel microspheres; S3, dissolving sodium alginate and acrylamide in water by stirring, adding methylene bisacrylamide, polyacrylamide, acid-base indicator and ammonium persulfate, mixing and dissolving thoroughly to obtain a mixed solution; S4, adding molybdenum disulfide gel microspheres to the mixed solution, and adding tetramethylethylenediamine and calcium sulfate dihydrate in sequence under continuous stirring, and stirring evenly; S5. After standing to solidify and removing impurities, a wound infection monitoring and repair gel dressing containing microspheres is obtained.
2. The method for preparing the microsphere-containing wound infection monitoring and repair gel dressing according to claim 1, characterized in that: The concentration of the molybdenum disulfide solution in S1 is 0.01 to 1 g / mL, and the concentration of the obtained sodium alginate solution is 0.025 to 0.6 g / mL.
3. The method for preparing the microsphere-containing wound infection monitoring and repair gel dressing according to claim 1, characterized in that: The volume ratio of the molybdenum disulfide solution to the sodium alginate solution added to S1 is 0.1:5-20.
4. The method for preparing the microsphere-containing wound infection monitoring and repair gel dressing according to claim 1, characterized in that: In S2, the molybdenum disulfide sodium alginate solution is injected into the calcium chloride solution at a flow rate of 0.02-1.0 mL / min by external force; the speed generated by the external force is 10.5-15.5 m / s.
5. The method for preparing the microsphere-containing wound infection monitoring and repair gel dressing according to claim 1, characterized in that: The mass percentage of the calcium chloride solution in S2 is 0.5% to 2.0%.
6. The method for preparing the microsphere-containing wound infection monitoring and repair gel dressing according to claim 1, characterized in that: In the mixed solution of S3, the concentration of sodium alginate is 0.01-0.04 g / mL, the concentration of acrylamide is 0.05-0.25 g / mL, the concentration of methylene bisacrylamide is 0.05-0.15 mg / mL, the concentration of polyacrylamide is 0.5-3 mg / mL, the concentration of acid-base indicator is 0.05-0.5 mg / mL, and the concentration of ammonium persulfate is 0.5-3 mg / mL.
7. The method for preparing the microsphere-containing wound infection monitoring and repair gel dressing according to claim 1, characterized in that: After S4 is stirred evenly, the concentration of molybdenum disulfide gel microspheres is 0.2-0.8 g / mL, the concentration of tetramethylethylenediamine is 0.3-2 μL / mL, and the concentration of calcium sulfate dihydrate is 0.001-0.01 g / mL.
8. A microsphere-containing wound infection monitoring and repair gel dressing, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 7.
9. The wound infection monitoring and repairing gel dressing containing microspheres according to claim 8, characterized in that: The microspheres are molybdenum disulfide gel microspheres, and the diameter thereof is 300-1000 μm.
10. An application of the wound infection monitoring and repair gel dressing containing microspheres as claimed in claim 9, characterized in that: The microsphere-containing wound infection monitoring and repair gel dressing is used in the preparation of wound treatment consumables.
Citation Information
Patent Citations
Wound dressing based on hydrogel-core-shell microspheres and preparation method thereof
CN110339393A
Temperature-sensitive hydrogel with visual diagnosis and treatment of infected wound and preparation method of hydrogel
CN111067862A
Composite polyacrylamide gel as well as preparation method and application thereof
CN113563534A
Antioxidant adhesive composite hydrogel as well as preparation method and application thereof
CN118593763A